The Strategic Involvement of Stakeholders in the Efficiency of Non-Profit Sport Organisations: From a Perspective of Survival to Sustainability - Dina Alexandra Marques Miragaia; Joao José de Matos Ferreira; Vanessa Ratten (BBR: Brazilian Business Review)
The objective of this study is to analyse the efficiency of non-profit sports clubs and identify the perceptions of their directors with regards to the stakeholders that exert the greatest influence over club efficiency levels. In order to analyse the efficiency of these clubs, we made recourse to the Data Envelopment Analysis (DEA) method. We also applied the Mann-Whitney test, to identify whether there are significant differences between efficient and non-efficient clubs with regards to the influence held by their stakeholders. We thus report that the majority of clubs operate efficiently. Both the efficient and the non-efficient clubs classify the club managers, members, sponsors, fans and athletes as the most important stakeholders to their efficiency levels. The results convey how there are no significant differences among the management team perceptions on the role of stakeholders in attaining club efficiency. The study also details the respective procedures that inefficient clubs should adopt in order to approximate the efficiency frontier.